Discurso eclesial y responsabilidad social - Jesús M. Carrasquilla Ospina (Franciscanum, 2013)
In the particular case of the Church, a comprehensive social responsibility could be stated, because it is concerned with human life in terms of total existence: «the glory of God is expressed in a worthy life for the man». Since the Church is present where life develops and looks for new challenges, it is important not to forget its transcendent vocation in history. The Church as a community will always be inspired and encouraged by the Holy Spirit’s action and its commitment to the poor and excluded is expressed in many of its social work, always following its moral foundation: the love of God for all his creation. That somehow, challenges us to take responsibility for everything we do with it. In other words, a profound experience of God of life should lead us to a historic compromise with our world and our society: the greatness of God is revealed in this story to give a new meaning to the human from the Incarnation.